2013
DOI: 10.5505/jkartaltr.2013.20438
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of relationship between body awareness, pain, emotional status and quality of life with healty people

Abstract: ÖzetAmaç: Bu çalışmada vücut farkındalık durumu ile ağrı, emosyonel durum ve yaşam kalitesi arasındaki ilişkinin incelenmesi amaçlandı. Gereç ve Yöntem:Çalışmada herhangi bir hastalığı olmayan 20-40 yaş arası 100 sağlıklı ve gönüllü katılımcı değerlendi-rildi. Ağrı durumu Görsel Ağrı Skalası (GAS) ile, emosyonel durum Beck Depresyon Ölçeğiyle, vücut farkındalık durumu Vücut Farkındalık Anketi (VFA) ile ve yaşam kalitesi SF-36 anketi ile değerlendirildi. Bulgular:Katılımcıların yaş ortalaması 36.88±10.45 yıl id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…They concluded that body awareness and body sensitivity decreased in patients with chronic pain. Erden and colleagues [58] investigated the relationship between body awareness, quality of life, and pain and found that body awareness had a positive effect on quality of life and a negative relationship with pain. This article is the second to explore the link between PD and body awareness.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that body awareness and body sensitivity decreased in patients with chronic pain. Erden and colleagues [58] investigated the relationship between body awareness, quality of life, and pain and found that body awareness had a positive effect on quality of life and a negative relationship with pain. This article is the second to explore the link between PD and body awareness.…”
Section: Discussionmentioning
confidence: 99%
“…A study involving healthy individuals reported an inverse association between body awareness and pain intensity and emotional state. 14 In older adults, chronic musculoskeletal pain and cognitive impairment are reduced body awareness. 8 Hider et al 25 reported that body totality was associated with disease acceptance in patients with ankylosing spondylitis and that body image, including body totality and body selfconsciousness, was inversely related to depression.…”
Section: Discussionmentioning
confidence: 99%
“…12 Many cortical areas are interconnected to help the perception of body position, the relationship between body segments and the body itself, and body awareness, which is the ability to recognize one's own body, is formed. 13 Previous studies have suggested a negative relationship between body awareness, pain and emotional mood in healthy individuals 14 and that cognitive impairment and chronic musculoskeletal pain reduce body awareness in older adults. 8 Shifting the focus of attention from pain sensations to different mental tasks may be beneficial in reducing pain, indeed, previous studies on experimental pain or other models of acute pain show such benefits.…”
Section: Introductionmentioning
confidence: 99%
“…The participant was asked to give a score between one to seven for each statement. Higher scores obtained from the questionnaire indicate better body awareness [20,21].…”
Section: Assessment Protocolmentioning
confidence: 99%